Interest Rate Rules and Macroeconomic Stability under Heterogeneous Expectations - Mikhail Anufriev; Tiziana Assenza; Cars Hommes; Domenico Massaro (Tinbergen Institute, 2009)
The recent macroeconomic literature stresses the importance of managing heterogeneous expectations in the formulation of monetary policy. We use a stylized macro model of Howitt (1992) to investigate inflation dynamics under alternative interest rate rules when agents have heterogeneous expectations and update their beliefs based on past performance as in Brock and Hommes (1997). The stabilizing effect of different monetary policies depends on the ecology of forecasting rules, on agents' sensitivity to differences in forecasting performance and on how aggressively the monetary authority sets the nominal interest rate in response to inflation. In particular, if the monetary authority only responds weakly to inflation, a cumulative process with rising inflation is likely. On the other hand, a Taylor interest rate rule that sets the interest rate more than point for point in response to inflation stabilizes inflation dynamics, but does not always lead the system to converge to the rational expectations equilibrium as multiple equilibria may persist, even when a fully rational, but costly, expectations rule is part of the ecology of forecasting strategies.
Keywords: E52; D83; D84; C62; 330; Heterogeneous Expectations; Monetary Policy; Cumulative Process; Taylor Rule; Inflationserwartung; Beschränkte Rationalität; Taylor-Regel; Gleichgewicht; Theorie